Functional roles of root plasticity and its contribution to water uptake and dry matter production of CSSLs with the genetic background of KDML105 under soil moisture fluctuation. (3rd July 2018) - Owusu-Nketia, Stella; Siangliw, Jonaliza Lanceras; Siangliw, Meechai; Toojinda, Theerayut; Vanavichit, Apichart; Ratsameejanphen, Noppon; Ruangsiri, Mathurada; Sriwiset, Sararin; Suralta, Roel Rodriguez; Inukai, Yoshiaki; Mitsuya, Shiro; Kano-Nakata, Mana; et al.
ABSTRACT: Soil moisture fluctuation (SMF) stress due to erratic rainfall in rainfed lowland (RFL) rice ecosystems negatively affect production. Under such condition, root plasticity is one of the key traits that play important roles for plant adaptation. This study aimed to evaluate root plasticity expression and its functional roles in water uptake, dry matter production and yield under SMF using three chromosome segment substitution lines (CSSLs) with major genetic background of KDML105 and a common substituted segment in chromosome 8. The CSSLs showed greater shoot dry matter production than KDML105 under SMF, which was attributed to the maintenance of stomatal conductance resulting in higher grain yield. The root system development based on total root length of the CSSLs were significantly higher than that of KDML105 due to the promoted production of nodal and lateral roots. These results implied that the common substituted segments in chromosome 8 of the 3 CSSLs may be responsible for the expression of their root plasticity under SMF and contributed to the increase in water uptake and consequently dry matter production and yield. These CSSLs could be used as a good source of genetic material for drought resistance breeding programs targeting rainfed lowland condition with fluctuating soil moisture environments and for further genetic studies to elucidate mechanisms underlying root plasticity.